The Manner Of Question In Collection (HISAR L MADAEH ALBAHER) For Mahmoud Darwish (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research studies the denotations and the meanings that the manner of question, contained in collection (HISAR L MADAEH ALBAHER) For Mahmoud Darwish poet, because it was known that this manner does not stay by the syntax's denotation limits (the meaning of asking), but it crosses that limits to other and many denotations that the context demands such as: hindering, disapproving, denying, touching, and admitting…etc.This research will deal with this denotations in the collection by citing syllables poetry , and elaborates the new denotation that manner of question contained,  by studying every syllable poetry analyzing study, bases on building of poetry text, from this study we will conclude the  denotation.